2018
DOI: 10.2106/jbjs.17.01485
|View full text |Cite
|
Sign up to set email alerts
|

Extended Oral Antibiotic Prophylaxis in High-Risk Patients Substantially Reduces Primary Total Hip and Knee Arthroplasty 90-Day Infection Rate

Abstract: Background: Total joint arthroplasty (TJA) episodic payment models shift risk and cost of periprosthetic joint infection (PJI) to surgeons and hospitals, causing some to avoid treating high-risk patients. Furthermore, there are little data to support optimization of host factors preoperatively to decrease PJI, and recent literature supports using extended antibiotic prophylaxis following reimplantation TJA. The purpose of this study was to evaluate whether extended oral antibiotic prophylaxis minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 36 publications
1
94
0
1
Order By: Relevance
“…We have previously reported that bacterial aggregates are present during periprosthetic joint infection [11]. Nearly 50% of S. aureus PJI infections exhibit antibiotic tolerance, and the development of S. aureus aggregates enhances tolerance towards antibiotics and the host immune system [6,12,23,24,[39][40][41]. Herein, we utilized a novel method for precise quantification of synovial fluid induced aggregation using flow cytometry (Figs 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that bacterial aggregates are present during periprosthetic joint infection [11]. Nearly 50% of S. aureus PJI infections exhibit antibiotic tolerance, and the development of S. aureus aggregates enhances tolerance towards antibiotics and the host immune system [6,12,23,24,[39][40][41]. Herein, we utilized a novel method for precise quantification of synovial fluid induced aggregation using flow cytometry (Figs 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Inabathula et al 59 published a retrospective cohort study comparing an extended oral antibiotic protocol for 7 days to standard perioperative antibiotic administration following elective TJA in groups of patients with high‐risk comorbidities. They found significantly reduced rates of PJI using this protocol with a 1% infection rate in the extended antibiotic group vs 2.2% in the perioperative administered group alone 59 . While this is promising data, others have been critical of the methodology, and the potential global health impact of widespread adoption of these protocols need to be balanced with maintaining appropriate antibiotic stewardship 60 …”
Section: New Advancements In Prevention Of Pjimentioning
confidence: 99%
“…In a retrospective cohort study examining 2181 arthroplasties, Inabathula et al [33] investigated whether extended oral antibiotic prophylaxis reduced PJI in high-risk patients. Classification as high risk was determined at a coordinated care conference based on factors including BMI > 35, diabetes, smoking, chronic renal failure, autoimmune disease and colonization with MRSA.…”
Section: Duration Of Antibiotic Prophylaxismentioning
confidence: 99%